2012
DOI: 10.1190/geo2011-0196.1
|View full text |Cite
|
Sign up to set email alerts
|

Constrained full-waveform inversion by model reparameterization

Abstract: The waveform inversion problem is inherently ill-posed. Traditionally, regularization schemes are used to address this issue. For waveform inversion, where the model is expected to have many details reflecting the physical properties of the Earth, regularization and data fitting can work in opposite directions: the former smoothing and the latter adding details to the model. We propose constraining estimated velocity fields by reparameterizing the model. This technique, also called model-space preconditioning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…Similar to the methodology of Wang and Tsvankin (2013), we apply image-guided smoothing (Hale, 2009) to the VSP-data gradients to propagate the updates away from the borehole locations. This approach is close to that described by Guitton et al (2012) for isotropic FWI. The gradients are used in the L-BFGS (Nocedal and Wright, 2006) model-updating algorithm.…”
Section: Inversion Algorithmmentioning
confidence: 61%
“…Similar to the methodology of Wang and Tsvankin (2013), we apply image-guided smoothing (Hale, 2009) to the VSP-data gradients to propagate the updates away from the borehole locations. This approach is close to that described by Guitton et al (2012) for isotropic FWI. The gradients are used in the L-BFGS (Nocedal and Wright, 2006) model-updating algorithm.…”
Section: Inversion Algorithmmentioning
confidence: 61%
“…The relationship between d and P is dðx; t; x s Þ ¼ Pðx; t; x s Þj x¼x r . Some preconditioning methods can also be applied to the gradient to improve the convergence and to mitigate the nonlinearity of the inverse problem, for example, smoothing and/or filtering the gradient in the wavenumber domain (Nemeth et al, 1997;Guitton et al, 2012;Ma et al, 2012) and using depth-dependent weights for the gradient (Shipp and Singh, 2002;Wang and Rao, 2009). Moreover, the gradient can be normalized by the amplitude of the forward wavefield to approximately account for geometrical divergence (Gauthier et al, 1986) …”
Section: Objective Functionmentioning
confidence: 99%
“…At further expanse, the application of gradient-based methods allows for updating model m est in several linear iterations (e.g., Pratt, Shin and Hicks 1998). Therefore, the building of model m est is fully integrable with full-waveform inversion technology (e.g., Tarantola 1984;Pratt 1999;Plessix 2006;Virieux and Operto 2009;Zhu et al 2009), which has shown to produce high-resolution models in recent case studies (e.g., Sirgue et al 2010;Vigh et al 2010;Guitton, Ayeni and Díaz 2012). Alternatively, tools in velocity model building based on the input of a human interpreter can be used for creating a model with sharp interfaces.…”
Section: Wavefield Extrapolationmentioning
confidence: 99%